1979
DOI: 10.1136/gut.20.8.709
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes in the jejunal mucosa of dogs with naturally occurring exocrine pancreatic insufficiency

Abstract: SUMMARY The roles of extracellular and intracellular mechanisms in the degradation of brush border proteins have been investigated by studying the small intestinal mucosa of dogs with naturally occurring exocrine pancreatic insufficiency. Peroral jejunal biopsies were homogenised and the organelles separated by isopycnic centrifugation on continuous sucrose density gradients. The distributions of marker enzymes for the principal subcellular organelles were determined in the gradients and related to the specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1982
1982
1996
1996

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The large oligosaccharidases are removed from the surface of the enterocytes by pancreatic enzymes [11]. Increased sucrase and maltase, but not lactase, activity has been observed in dogs [12] and in humans [13] with pancreatic insufficiency. The slight diminution seen after the fifth day may depend on the lack of substrate.…”
Section: Discussionmentioning
confidence: 99%
“…The large oligosaccharidases are removed from the surface of the enterocytes by pancreatic enzymes [11]. Increased sucrase and maltase, but not lactase, activity has been observed in dogs [12] and in humans [13] with pancreatic insufficiency. The slight diminution seen after the fifth day may depend on the lack of substrate.…”
Section: Discussionmentioning
confidence: 99%
“…A previous in vitro study had suggested that jejunal malabsorption of neutral amino acids might be because of a defect intrinsic to cystic fibrosis.4 In our study the defect in phenylalanine absorption was also present in patients with other forms of pancreatic insufficiency suggesting perhaps that pancreatic insufficiency per se was involved. There is evidence that pancreatic proteolytic enzymes22 23 and mucosal lysosomal hydrolases24 play a role in the turnover of brush border proteins, and thus may modulate brush border function. It is tempting to speculate that the present data could be explained on the basis of a reduction in the number of brush border transport sites, which also functioned less efficiently.…”
Section: Discussionmentioning
confidence: 99%
“…Results are expressed in the form of frequencydensity histograms the averaging of distributions being performed by computer.27 Marker enzymes for the principal subcellular organelles were assayed as described previously 26 28 Maltase, sucrase, and lactase were assayed29 in portions of biopsies collected in deionised water and disrupted in a Dounce homogeniser (Kontes Glass Co, Vineland, New Jersey, USA) with 20 strokes of a type B pestle. Protein was determined according to Schacterle and Pollack3" with bovine serum albumin (Armour Pharmaceutical Co, Chicago, USA) as standard.…”
Section: Biochemical Studiesmentioning
confidence: 99%